Determinants of agro pastoralists participation in irrigation scheme: the case of fentalle agro pastoral district, oromia regional state, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2016)
This paper analyzed the factors determining participation in irrigation project on agro pastoral household and their perception towards the scheme. The study result depends on cross-sectional data collected from a sample of 144 households of which 72 irrigation users and 72 non-users using a combination of multistage, stratified and random sampling. The data were analyzed using descriptive statistics and logistic regression to assess factors that affect participation in irrigation. Result revealed that agro pastoralists do have medium to very strong perception towards different aspects of irrigation performance indicator variable. It is observed that among the variables in logistic regression age, sex, income, input use and participation in cooperative organization have affected participation significantly and positively, while, farm experience, distance to the district market, and total livestock unit, affected participation in irrigation significantly and negatively. The study has also substantiated that irrigation in the study area has significant role on income and recommend that it shall be great and rewarding if policy makers, designers, implementers, and any funding agencies with similar interest. Further, capitalize and scale up the project to achieve the development plan and objective.Int. J. Agril. Res. Innov. & Tech. 5 (2): 44-50, December, 2015